Co-development enables holistic digital traceability of sustainability. The case of Peruvian cocoa - Hidalgo, Francisco; Jones, Sarah K.; Sanchez, Andrea; Ivanova, Yovita; Sánchez Choy, José G.; Mockshell, Jonathan; Steinke, Jonathan (2025)
Key messages: Policy shifts toward agroecology and growing consumer awareness have made holistic sustainability monitoring increasingly relevant. Advancements in digital technologies create favorable conditions for developing digital traceability tools to respond to this need. Digital traceability can facilitate data collection on agroecological metrics and end-to-end traceability. Technologies such as blockchain can make information management more transparent, reliable, and safe. End-to-end traceability requires the cooperation of different stakeholders and a system that integrates their information needs and capabilities while providing indicators that can be used to assess agrifood value chain sustainability. Here, we show a co-development approach proved to be an effective way to meet these requirements. Co-development involved addressing participants’ diversity of perspectives, interests, and capabilities. Several challenges arose, which required adaptive planning. Translation and mediation strategies were effective in navigating this environment. The use of a compact, yet holistic, set of agroecological metrics, and implementation of iterative programming and testing cycles with end-users, were key attributes to achieving systems’ contextualization and applicability. Identifying effective incentives, and removing barriers, is key to ensuring participation in co-development processes. Enabling holistic digital traceability calls for financial sustainability schemes that do not burden producers, and practices for managing data responsibly.